Diagnostic and Therapeutic Potential of Exosomes in Neurodegenerative Diseases - Gao, Panyue; Li, Xinrong; Du, Xinzhe; Liu, Sha; Xu, Yong (Frontiers in Aging Neuroscience, 2021)
Neurodegenerative diseases are closely related to brain function and the progression of the diseases are irreversible. Due to brain tissue being not easy to acquire, the study of the pathophysiology of neurodegenerative disorders has many limitations—lack of reliable early biomarkers and personalized treatment. At the same time, the blood-brain barrier (BBB) limits most of the drug molecules into the damaged areas of the brain, which makes a big drop in the effect of drug treatment. Exosomes, a kind of endogenous nanoscale vesicles, play a key role in cell signaling through the transmission of genetic information and proteins between cells. Because of the ability to cross the BBB, exosomes are expected to link peripheral changes to central nervous system (CNS) events as potential biomarkers, and can even be used as a therapeutic carrier to deliver molecules specifically to CNS. Here we summarize the role of exosomes in pathophysiology, diagnosis, prognosis, and treatment of some neurodegenerative diseases (Alzheimer’s Disease, Parkinson’s Disease, Huntington’s Disease, Amyotrophic Lateral Sclerosis).